2018
DOI: 10.1111/ppa.12941
|View full text |Cite
|
Sign up to set email alerts
|

The Brachypodium distachyon UGT Bradi5gUGT03300 confers type II fusarium head blight resistance in wheat

Abstract: Fusarium head blight (FHB), caused by fungi belonging to the Fusarium genus, is a widespread disease of wheat (Triticum aestivum) and other small‐grain cereal crops. The main causal agent of FHB, Fusarium graminearum, produces mycotoxins mainly belonging to type B trichothecenes, such as deoxynivalenol (DON), that can negatively affect humans, animals and plants. DON detoxification, mainly through glucosylation into DON‐3‐O‐glucose, has been correlated with resistance to FHB. A UDP‐glucosyltransferase from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Carbon cycling requires a variety of carbohydrate-active enzymes 33 , including GTs 34 . Some GTs in wheat root environments could help resist pathogenic fungi 35 , whereas other GTs had a self-detoxification mechanism 36 . Also, some GTs could catalyze the activation of hormones in plants and improve the transport efficiency of sugars in roots 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Carbon cycling requires a variety of carbohydrate-active enzymes 33 , including GTs 34 . Some GTs in wheat root environments could help resist pathogenic fungi 35 , whereas other GTs had a self-detoxification mechanism 36 . Also, some GTs could catalyze the activation of hormones in plants and improve the transport efficiency of sugars in roots 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Barley HvUGT13248 and its homolog Bradi5g03300 in B . distachyon were introduced into wheat by different research groups, and all of the data showed that expression of these genes increased FHB resistance and root tolerance to DON in wheat ( Li et al, 2015 , 2017 ; Pasquet et al, 2016 ; Gatti et al, 2019 ). For wheat UGT s, only two of them, i.e., TaUGT3 and TaUGT5 were introduced into wheat to functionally confirm their role in FHB resistance ( Xing et al, 2018 ; Zhao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genes contributing to FHB resistance have been introduced from alien species using transgenic approaches for over 20 years (Ma et al, 2020). These include the pathogenesis-related (PR) gene, ScNPR1 (Secale cereale-NPR1) from rye (Yu et al, 2017), overexpression of barley HvUGT13248 and Brachypodium distachyon UGT Bradi5gUGT03300 for improved detoxification of DON to D3G and NIV to NIV3G respectively (Li et al, 2015;Gatti et al, 2019), and introduction of barley class II chitinase gene for enhancing Type II and III resistance in wheat (Shin et al, 2008). Despite the daunting efforts, only limited success has been achieved to engineer transgenes in greenhouse environments, which also need further verification under field conditions to validate its functionality and genetic stability.…”
Section: Modern Genomic Approaches For Breeding Fhb Resistancementioning
confidence: 99%
“…The early signaling pathways for SAR, mediated by coordinated and ordered expression of SA, jasmonic acid, ethylene, calcium ions, phosphatidic acid, and phenylpropanoid in addition to reactive oxygen species (ROS) production and scavenging, programmed cell death, cell wall fortification, and lignin biosynthesis have been widely discussed (Ding et al, 2011;Ma et al, 2020). The ability of the host plant to curb F. graminearum infection through the production of detoxification enzymes as observed in recent studies is another important approach to understand FHB resistance mechanisms (Lemmens et al, 2005;Gatti et al, 2019;Wang et al, 2020).…”
Section: Molecular Mechanisms Of Fhb Resistancementioning
confidence: 99%